In Vitro and In Vivo Evaluations of Cytochrome P450 1A2 Interactions with Duloxetine - Lobo, Evelyn D.; Bergstrom, Richard F.; Reddy, Shobha; Quinlan, Tonya; Chappell, Jill; Hong, Quan; Ring, Barbara; Knadler, Mary Pat (Clinical pharmacokinetics, 2008)
Objective: To determine whether duloxetine is a substrate, inhibitor or inducer of cytochrome P450 (CYP) 1A2 enzyme, using in vitro and in vivo studies in humans. Methods: Human liver microsomes or cells with expressed CYP enzymes and specific CYP inhibitors were used to identify which CYP enzymes catalyse the initial oxidation steps in the metabolism of duloxetine. The potential of duloxetine to inhibit CYP1A2 activity was determined using incubations with human liver microsomes and phenacetin, the CYP1A2 substrate. The potential for duloxetine to induce CYP1A2 activity was determined using human primary hepatocytes treated with duloxetine for 72 hours. Studies in humans were conducted using fluvoxamine, a potent CYP1A2 inhibitor, and theophylline, a CYP1A2 substrate, as probes. The subjects were healthy men and women aged 18–65 years. Single-dose duloxetine was administered either intravenously as a 10-mg infusion over 30 minutes or orally as a 60-mg dose in the presence or absence of steady-state fluvoxamine (100 mg orally once daily). Single-dose theophylline was given as 30-minute intravenous infusions of aminophylline 250 mg in the presence or absence of steady-state duloxetine (60 mg orally twice daily). Plasma concentrations of duloxetine, its metabolites and theophylline were determined using liquid chromatography with tandem mass spectrometry. Pharmacokinetic parameters were estimated using noncompartmental methods and evaluated using mixed-effects ANOVA. Safety measurements included vital signs, clinical laboratory tests, a physical examination, ECG readings and adverse event reports. Results: The in vitro results indicated that duloxetine is metabolized by CYP1A2; however, duloxetine was predicted not to be an inhibitor or inducer of CYP1A2 in humans. Following oral administration in the presence of fluvoxamine, the duloxetine area under the plasma concentration-time curve from time zero to infinity (AUC ∞ ) and the maximum plasma drug concentration (C max ) significantly increased by 460% (90% CI 359, 584) and 141% (90% CI 93, 200), respectively. In the presence of fluvoxamine, the oral bioavailability of duloxetine increased from 42.8% to 81.9%. In the presence of duloxetine, the theophylline AUC ∞ and C max increased by only 13% (90% CI 7, 18) and 7% (90% CI 2,14), respectively. Coadministration of duloxetine with fluvoxamine or theophylline did not result in any clinically important safety concerns, and these combinations were generally well tolerated. Conclusion: Duloxetine is metabolized primarily by CYP1A2; therefore, coadministration of duloxetine with potent CYP1A2 inhibitors should be avoided. Duloxetine does not seem to be a clinically significant inhibitor or inducer of CYP1A2; therefore, dose adjustment of CYP1A2 substrates may not be necessary when they are coadministered with duloxetine.